Skin blister formation together with patterned intradermal hematoma: A special type of tire mark injury in victims run over by a wheel. (April 2015) - Pircher, R.; Epting, T.; Schmidt, U.; Geisenberger, D.; Pollak, S.; Kramer, L.
Abstract: A traffic accident victim run over by a vehicle may show a patterned skin hematoma reflecting the grooves of the tire's profile. Apart from this well-known type of imprint mark, the affected skin can also be blistered provided that the wheel exerts high pressure on the body for a prolonged period of time. The macro- and micromorphological findings as well as the protein composition of the blister fluid were investigated on the basis of a relevant autopsy case. Analogous to blisters associated with hanging marks, the transudation of serous fluid with consecutive detachment of the epidermis is interpreted as a pressure-related effect which cannot be regarded as a sign of vitality.